Pengalaman Paramadina sebagai Rumah Pengetahuan Berbasis Nilai-nilai Ketuhanan, Tradisi Hikmah, dan Ilmu Pengetahuan - Sabri, Muhammad; Ikhsan, Muh; Wekke, Ismail Suardi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2018)
This article describes Paramadina University, a higher educational institution in Indonesia, which cannot be separated from its leader as well as the founder of its initial idea, i.e. Nurcholish Madjid. The existence of Paramadina University is, therefore, more closely related to the establishment of Nurcholish Madjid?s genial ideas who attempted to link the idea of ??Islam-Modernity-Indonesia. Since its initial inauguration in 1994, Paramadina University has carried out basic insights aimed at building a scientific society based on divine values and wisdom of humanity. It also encourages the values of pioneering souls to break through the borders of knowledge. Employing qualitative approach, this article aims at further analyzing the model of modern religious tradition developed by Paramadina University. The study affirms central position and role played by this higher educational institution both in Indonesia and the Islamic world in general. This centrality appears, especially, when we link the ideas of Islamic universalism, spatial-temporal of indonesianess, along with responses toward the life of the contemporary society which seems to be not only complex but also moves quickly escorting the breath of the age.